2014
DOI: 10.4161/15548627.2014.993283
|View full text |Cite
|
Sign up to set email alerts
|

A novel cytostatic form of autophagy in sensitization of non-small cell lung cancer cells to radiation by vitamin D and the vitamin D analog, EB 1089

Abstract: The standard of care for unresectable lung cancer is chemoradiation. However, therapeutic options are limited and patients are rarely cured. We have previously shown that vitamin D and vitamin D analogs such as EB 1089 can enhance the response to radiation in breast cancer through the promotion of a cytotoxic form of autophagy. In A549 and H460 non-small cell lung cancer (NSCLC) cells, 1,25-D3 (the hormonally active form of vitamin D) and EB 1089 prolonged the growth arrest induced by radiation alone and suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 50 publications
3
72
0
Order By: Relevance
“…216 In this perspective, a fundamental role should be exerted by mitochondria. 217,218 As previously reported, cytosolic calcium may inhibit autophagy, while a calcium increase promotes apoptosis. 18,219 As a modulating factor, calcium signaling has a major role in autophagy through the activity of the Ca 2þ /calmodulin-dependent kinase kinase beta, which activates AMP-activated protein kinase (AMPK), a mechanistic target of rapamycin-dependent autophagy, this latter being also a result of the promoting role of vitamin D. 217 The regulation of autophagy by VDR, together with further components such as AMPK and TP53, has been reported also in cancer models.…”
Section: Pro-survival Role Of Vitamin D Within the Cellmentioning
confidence: 65%
“…216 In this perspective, a fundamental role should be exerted by mitochondria. 217,218 As previously reported, cytosolic calcium may inhibit autophagy, while a calcium increase promotes apoptosis. 18,219 As a modulating factor, calcium signaling has a major role in autophagy through the activity of the Ca 2þ /calmodulin-dependent kinase kinase beta, which activates AMP-activated protein kinase (AMPK), a mechanistic target of rapamycin-dependent autophagy, this latter being also a result of the promoting role of vitamin D. 217 The regulation of autophagy by VDR, together with further components such as AMPK and TP53, has been reported also in cancer models.…”
Section: Pro-survival Role Of Vitamin D Within the Cellmentioning
confidence: 65%
“…As a backup strategy to inhibit tumor growth, cytostatic autophagy may overcome these barriers by inhibiting the growth of cancer cells regardless of their sensitivity to apoptosis (39,40). In support of this, very recently, it has been reported that the combination of radiotherapy with vitamin D inhibits cell proliferation through inducing cytostatic autophagy in non-small cell lung cancer cells (41). Our results revealed that autophagy induced by ivermectin has the capacity to inhibit breast cancer cell growth in a cytostatic way, suggesting that the use of ivermectin as an anticancer agent may reduce the self-renewal capacity and proliferation recovery in breast cancer cells.…”
Section: Discussionmentioning
confidence: 77%
“…We and others have reported that a primary response of tumor cells to radiation is autophagy [4447]. Figures 2A presents images of irradiated cells stained with acridine orange, which is indicative of autophagy while Figures 2B provides quantification of the extent of autophagy over a range of radiation doses.…”
Section: Resultsmentioning
confidence: 99%